A Geospatial Artificial Intelligence and satellite-based earth observation cognitive system in response to COVID-19. (August 2022) - Atek, Sofiane; Pesaresi, Cristiano; Eugeni, Marco; De Vito, Corrado; Cardinale, Vincenzo; Mecella, Massimo; Rescio, Antonello; Petronzio, Luca; Vincenzi, Aldo; Pistillo, Pasquale; Bianchini, Filippo; Giusto, Gianfranco; et al.
Abstract: The pandemic emergency caused by the spread of COVID-19 has stressed the importance of promptly identifying new epidemic clusters and patterns, to ensure the implementation of local risk containment measures and provide the needed healthcare to the population. In this framework, artificial intelligence, GIS, geospatial analysis and space assets can play a crucial role. Social media analytics can be used to trigger Earth Observation (EO) satellite acquisitions over potential new areas of human aggregation. Similarly, EO satellites can be used jointly with social media analytics to systematically monitor well-known areas of aggregation (green urban areas, public markets, etc.). The information that can be obtained from the Earth Cognitive System 4 COVID-19 (ECO4CO) are both predictive, aiming to identify possible new clusters of outbreaks, and at the same time supervisorial, by monitoring infrastructures (i.e. traffic jams, parking lots) or specific categories (i.e. teenagers, doctors, teachers, etc.). In this perspective, the technologies described in this paper will allow us to detect critical areas where individuals can be involved in risky aggregation clusters. The ECO4CO data lake will be integrated with ad hoc data obtained by health care structures to understand trends and dynamics, to assess criticalities with respect to medical response and supplies, and to test possibilities useful to tackle potential future emergencies. The System will also provide geographical information on the spread of the infection which will allow an appropriate context-specific public health response to the epidemic. This project has been co-funded by the European Space Agency under its Business Applications programme. Highlights: Integration of satellite Earth Observation with ground data for pandemic monitoring and medical resources optimization. Use of artificial intelligence for predictions of local epidemic behaviour. Identification of epidemic clusters in crowded areas and tracking potential spreads. Intelligent Satellite Tasking for new Earth Observation image acquisitions over identified candidate cluster areas. Identification and prevision of medical health needs and logistic supports.